Extracellular Vesicles in Psychiatry Research in the Context of RDoC Criteria - TOPUZOĞLU, AHMET; ILGIN, CAN (KOREAN NEUROPSYCHIATRIC ASSOC, 2018)
The analysis of extracellular vesicles has been accelerated because of the technological advancements in omics methods in recent decades. Extracellular vesicles provide multifaceted information regarding the functional status of the cells. This information would be critical in case of central nervous system cells, which are confined in a relatively sealed biological compartment. This obstacle is more dramatic in psychiatric disorders since their diagnosis primarily depend on the symptoms and signs of the patients. In this paper, we reviewed this rapidly advancing field by discussing definition of extracellular vesicles, their biogenesis and potential use as clinical biomarkers. Then we focused on their potential use in psychiatric disorders in the context of diagnosis and treatment of these disorders. Finally, we tried to combine the RDoC (Research Domain Criteria) with the use of extracellular vesicles in psychiatry research and practice. This review may offer new insights in both basic and translational research focusing on psychiatric
Keywords: Extracellular vesicle; Depression; Bipolar disorder; Schizophrenia; Research domain criteria; CENTRAL-NERVOUS-SYSTEM; ALZHEIMERS-DISEASE; BIPOLAR DISORDER; EXOSOMES; DEPRESSION; BRAIN; OLIGODENDROCYTES; MICROVESICLES; DYSFUNCTION; RECEPTORS